The Effect of Consumer Satisfaction on Loyalty and Word of Mouth in Fast Food Restaurants Among Gen Z - Amelia, Rika; Nisa, Puspita Chairun (PT Inovasi Pratama Internasional, 2025)
Customer satisfaction a very important role in marketing strategies that can be implemented by fast food restaurants by presenting high-quality menus and providing optimal service to consumers, fast food restaurants strive to create positive experiences that can increase customer trust. The purpose of this study was to determine how much influence customer satisfaction has on consumer loyalty and Word of Mouth in fast food restaurants among generation Z. This type of research is quantitative with a purposive sampling technique distributed through questionnaires fast food consumer’s restaurant respondents aged 18-27 years and domiciled in the Bekasi area. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that the food quality variable has the greatest direct influence on customer satisfaction, then the trust variable does not moderate the relationship between customer satisfaction and customer loyalty. This study contributes to fast food restaurants in maintaining and increasing customer satisfaction can be seen from several factors, namely prioritizing food quality as an effort to improve restaurant quality, especially related to the menu offered. High quality will provide greater customer satisfaction, of course it will be more in demand by generation Z. For further research, researchers plan to expand the research area and look for objects in other fields.